Bio-diritto e bio-politica. Il corpo e la legge nella filosofia di Michel Foucault (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
This paper is dedicated to the contribution that Michel Foucault’s philoso-phy can provide the definition of the epistemological status of bio-law. The essay is focused both on Foucault’s thesis on the birth of modern biology – elaborated dur-ing the Sixties – and on the critics to sovereignty theory of the following decade. Assuming at first this point of view, the paper examines the change of nature in juridical decisions on life, when life itself becomes an object of mechanical reproduction. According to this kind of problems, the paper aims to underline the difference between body and flesh in Michel Foucault’s political thought.
Keywords: Foucault; Politics; Law; Medicine; Death